2003
DOI: 10.1002/ejoc.200390081
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Synthesis of Racemic Spirocyclopropane‐Annelated 2‐Deoxyhexose Derivatives

Abstract: High‐pressure‐induced inverse‐electron‐demand hetero‐Diels−Alder reactions of ethyl trans‐4‐ethoxy‐2‐oxo‐3‐butenoate (2a) and methyl trans‐4‐benzyloxy‐2‐oxo‐3‐butenoate (2b) with benzyl (cyclopropylidenemethyl) ether (1) each yielded mixtures of two separable diastereomeric esters 7a (64%) and 7b (80%) which, in three subsequent steps, led to the 3‐ethylated and 3‐benzylated α‐ and β‐anomeric benzyl spiro[2‐deoxy‐(D,L)‐arabino‐hexopyranoside‐2,1′‐cyclopropanes] α‐10a,b and β‐10a,b, respectively. The relative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Recently, we found that [2+2] cycloadditions of (alkoxymethylene)cyclopropanes 1, which are easily accessible and storable at room temperature, [8] with imines proceeded at ambient pressure [Equation (1)]. [9] We envisioned that the formation of the zwitterionic intermediate A, in which the cation center is doubly stabilized by the cyclopropyl and the alkoxy groups, facilitated the cycloaddition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that [2+2] cycloadditions of (alkoxymethylene)cyclopropanes 1, which are easily accessible and storable at room temperature, [8] with imines proceeded at ambient pressure [Equation (1)]. [9] We envisioned that the formation of the zwitterionic intermediate A, in which the cation center is doubly stabilized by the cyclopropyl and the alkoxy groups, facilitated the cycloaddition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of t-BuOK or TEA as a base in this methodology has allowed products 58a-c to be obtained in good yields, as depicted in Scheme 24. [42] In particular, the highly strained and unusually tetrasubstituted alkene bicyclopropylidene 59 [8f,43] could be prepared by de Meijere et al in up to 82% yield starting from the corresponding 1-bromo-1-cyclopropylcyclopropane (Scheme 24). [44] In the last decade, a large number of nucleoside analogues based on a methylenecyclopropane structure have been synthesized by the group of Zemlicka with the aim of evaluating their broad-spectrum antiviral activities.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…After stirring at ambient temperature for 2 h, the reaction was quenched by addition of 5 % aqueous H 2 SO 4 (2 mL), the organic layer was separated, and the aqueous phase was re-extracted with diethyl ether (3 2 mL). The combined organic phases were washed with brine (2 5 mL) and dried with MgSO 4 . Solvent removal left a crude product, which was purified by chromatography on silica gel.…”
Section: General Procedures For Reaction Of 6 With Neutral Nucleophilementioning
confidence: 99%
“…A series of 1'-substituted methylenecyclopropane derivatives 1 (Scheme 1) has demonstrated a range of reactivity patterns potentially useful for the synthesis of certain natural products and spirocyclopropanated analogues of biologically active compounds. [2,3] For example, bicyclopropylidene (1a) has been employed in various palladium-catalyzed cascade reactions, [2] and (benzyloxymethylene)-cyclopropane (1b) was used in the synthesis of a spirocyclopropane-annelated sugar [4] as well as interesting azetidine derivatives. [5] Several previously prepared acceptor-substituted methylenecyclopropanes 1c-h come along with a particularly broad spectrum of applications.…”
Section: Introductionmentioning
confidence: 99%